Strategic Management / An Integrated Approach: Second Edition - Hill W. Charles; Jones Gareth R (Houghton Mifflin Company, 1992)
Preface, Introduction, The Strategic Management Process, Corporate Mission and Goals and Stakeholders, Strategy Formulation, Analyzing the External Environment: The Identification of Opportunities and Threats, Internal Analysis: Strengths and Weaknesses and Distinctive Competencies, Business-Level Strategy, Business-Level Strategy and Industry Structure, Corporate-Level Strategy: Vertical Integration and Diversification, Corporate-Level Strategy: The Global Dimension, Analyzing and Changing the Corporate Portfolio, Strategic Implementation, Designing Organizational Structure, Choosing Integration and Control Systems, Matching Structure and Control to Strategy, Conflict and Politics and Change in Strategy-Structure Choice, Case Study Analysis, Analyzing and Writing a Case Study, Cases, Index.
Preface, Introduction, The Strategic Management Process, Corporate Mission and Goals and Stakeholders, Strategy Formulation, Analyzing the External Environment: The Identification of Opportunities and Threats, Internal Analysis: Strengths and Weaknesses and Distinctive Competencies, Business-Level Strategy, Business-Level Strategy and Industry Structure, Corporate-Level Strategy: Vertical Integration and Diversification, Corporate-Level Strategy: The Global Dimension, Analyzing and Changing the Corporate Portfolio, Strategic Implementation, Designing Organizational Structure, Choosing Integration and Control Systems, Matching Structure and Control to Strategy, Conflict and Politics and Change in Strategy-Structure Choice, Case Study Analysis, Analyzing and Writing a Case Study, Cases, Index.